If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(-3) = -2x + 3 Reorder the terms for easier multiplication: -3f = -2x + 3 Reorder the terms: -3f = 3 + -2x Solving -3f = 3 + -2x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by '-3'. f = -1 + 0.6666666667x Simplifying f = -1 + 0.6666666667x
| -5(X+3)+2x=45 | | 0.4x-0.8(5-x)=1.4 | | 4x^2-9x+13=8x+9 | | (4a^2-7ab)*2a^3b= | | 3X+9=-4x+25 | | x+(x+200)+3(x+200)=1575 | | C=12x+25findx | | 5(x+5)=-36 | | 3(n-6)+n=4-2(n-1) | | V-9=-10 | | x+(x+200)+3(x+200)=1775 | | 5.2+0.7=2.8+2.2 | | x+(x+200)+3(x+200)= | | -16+y=2y | | 3(z-7)=12 | | 2.49+1.24b=11.17 | | 3g+5=21+g | | 4=-2x+5x+4 | | 3(5)-3x=9 | | 3(2-7)=12 | | 64-2x=75-3x | | 9x+4-5x=-18 | | 8(k-8)=8k-24 | | -18m=92 | | -k+18=15 | | 2x^2+2y^2+8x-8y-2=0 | | X+(x-1081)=213483 | | 92=-18m | | (17x-y)+(12x+4y)+90=180 | | 8x-3x-10=222 | | -1+3(a+4)=11+3a | | 2+2.4w=-10 |